Tetrahydropyrazolopyridines as antifriction and antiwear agents: Experimental and DFT calculations - Kavita; Verma P.; Verma D.K.; Kumar B.; Singh A.K.; Shukla N.; Srivastava V.; Rastogi R.B. (My University, 2025)
Some tetrahydropyrazolopyridines (THPP-H) with the methoxy (THPP-OMe) and methyl (THPP-Me) substituents were synthesized by a one-pot multi-component reaction. NMR spectroscopy (1H and 13C) was used to authenticate the synthesis. According to the results of tribological tests ASTM D4172, and ASTM D5183 on a four-ball tester in paraffin oil (PO) at a concentration of 0.25% w/v, their relative tribo-activity along with a reference additive, zinc dialkyldithiophosphate (ZDDP) could be figured out as mentioned below-THPP-OMe > THPP-Me > THPP-H > ZDDP. The calculation of frictional power loss from the coefficient of friction data of the tested additives supports the given order. As is apparent from AFM and SEM micrographs of the wear scar surface for plain oil with and without different tetrahydropyrazopyridines, surface evenness endorses the above trend. Proof for strong adsorption of the synthesized additives is provided by EDX analysis of the steel ball surface after performing the tribological test, where nitrogen and oxygen are vividly seen as heteroatoms. XPS studies reveal the composition of the in situ formed tribofilm. The moieties containing carbon bonded to oxygen/nitrogen as decomposed products of the additive together with oxides of iron in +II or +III oxidation states are perceptible in the tribofilm, the tribofilm interferes with the proximity of the surfaces keeping them far apart. Consequently, friction and wear are remarkably reduced. Findings from Density Functional Theory (DFT) calculations are in full agreement with the results obtained from tribological experiments. This journal is © The Royal Society of Chemistry.